2022
DOI: 10.1111/ene.15363
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral small vessel disease and prognosis in intracerebral haemorrhage: A systematic review and meta‐analysis of cohort studies

Abstract: Background and purpose The aim was to investigate whether cerebral small vessel disease (CSVD) markers and the total CSVD burden are associated with functional outcome, mortality, stroke recurrence and haematoma expansion in patients with spontaneous intracerebral haemorrhage (ICH). Methods Following a previously registered protocol (PROSPERO protocol: CRD42021287743), PubMed, Web of Science and Embase were systematically searched to identify relevant literature up to November 2021. Cohort studies that examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 89 publications
(138 reference statements)
0
12
0
Order By: Relevance
“…Computed tomography can assess several CSVD markers, including leukoaraiosis, lacune and brain atrophy ( 17 ). These markers may be useful for identifying patients at higher risk of intracerebral hemorrhage ( 18 ). Although magnetic resonance imaging is typically used to evaluate CSVD markers, CT offers faster assessment, which can be critical in time-sensitive situations such as IVT for AIS ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Computed tomography can assess several CSVD markers, including leukoaraiosis, lacune and brain atrophy ( 17 ). These markers may be useful for identifying patients at higher risk of intracerebral hemorrhage ( 18 ). Although magnetic resonance imaging is typically used to evaluate CSVD markers, CT offers faster assessment, which can be critical in time-sensitive situations such as IVT for AIS ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…They are usually symmetrically distributed in the white matter including the pons and brain stem on imaging, and also in the deep gray matter(Wu et al, 2022;Hu et al, 2022). White matter hyperintensities (WMH) are the most important predictors of gait dysfunction, and more severe WMH-related defects are located in the internal capsule, Centrum semiovale), periventricular frontal lobe, etc(Rudilosso et al, 2022;Cheng et al, 2022). The number of lacunar infarcts is a predictor of executive dysfunction, presumably due to damage to the frontal-subcortical circuit, decreased connectivity and metabolism within the prefrontal cortex, and ultimately executive dysfunction(Huang et al, 2022;Tian et al, 2022).…”
mentioning
confidence: 99%
“…31 However, other than its potential diagnostic utility, evidence on PVS's prognostic value is still scarce, especially in CAA, and its clinical value remains undefined. A recent meta-analysis found that PVS were not associated with post-ICH prognosis, 96 but previous studies indicate an association between high burden of CSO-PVS and risk of recurrent ICH. 103,104 Recent investigations in CAA do not report a significant association between PVS and cognitive performance, 53,105 but in population-based studies, higher burden of PVS has been associated with worse cognition and increased risk of dementia.…”
Section: Cortical CMImentioning
confidence: 96%
“…95 In patients with ICH, lacunes were associated with worse functional outcomes and increased recurrence. 96 Specific prognostic data on CAA patients is scarce.…”
Section: Css/sahmentioning
confidence: 99%
See 1 more Smart Citation